Behaviour of rainfall over lakes around Bombay - KUMAR, SURENDER; BHAN, S. C. (MAUSAM, 1995)
Analysis of monthly rainfall brings out two distinctly different areas of rainfall affinity-one comprising of the lakes situated in Greater Bombay and the other in Thane districts. Rainfall of different sub-periods/months was found to be independent of the rainfall of preceding sub-periods/months. Multiple regression equations between lake levels and monthly rainfall have been computed to predict the anticipated lake levels at the end of different months.